THE EFFECTIVENESS OF AGARWOOD INDUCTION BY FUNGAL INOCULATION ON Gyrinops versteegii - Lutfi Anggadhania; Y.M.M. Anita nugraheni; Nurul Wahyuni (Jurnal Perbenihan Tanaman Hutan, 2022)
Agarwood commerce increases as a result of its high market value. Due to the length of time required for agarwood to develop in nature, the supply cannot meet market demand. A variety of methods for growing and inoculating agarwood were being developed. This research aimed to determine the efficacy of inoculating Gyrinops versteegii with agarwood-producing fungus from West Nusa Tenggara in Lombok. The methodology used in this study is bio-induction with drilling on the stems of Gyrinops versteegii trees. The agarwood inoculant was then applied to the perforated and then covered with paraffin. Inoculants used in this study were fungi isolated from the agarwood tree G. verstegii found in West Nusa Tenggara. The fungal inoculants were re-inoculated on identical agarwood trees in a similar environment to the origin of the isolate. This agarwood inoculation study is intended to improve agarwood's overall quality. Inoculating agarwood with isolates obtained from the same species of agarwood tree improved the compatibility between the isolates and agarwood-producing plants. After 6 months of inoculation, the findings revealed that the mean area with high infection in fungal isolates code LT was 2728 mm2, while code M, code ALS, and the control isolates had respective values of 543 mm2, 281.3 mm2, and 166 mm2. The olfactory and color characteristics of each isolating agent showed no significant differences. The efficacy of LT fungal isolates is 73%, but the effectiveness of ALS and M fungal isolates is 7% and 14%, respectively. The effectiveness (p≤0.05) is shown by the area parameter.